2015
DOI: 10.1101/016402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteomic analysis of Dhh1 complexes reveals a role for Hsp40 chaperone Ydj1 in yeast P-body assembly

Abstract: P-bodies (PB) are ribonucleoprotein (RNP) complexes that aggregate into cytoplasmic foci when cells are exposed to stress. While the conserved mRNA decay and translational repression machineries are known components of PB, how and why cells assemble RNP complexes into large foci remain unclear. Using mass spectrometry to analyze proteins immunoisolated with the core PB protein Dhh1, we show that a considerable number of proteins contain low-complexity (LC) sequences, similar to proteins highly represented in m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 110 publications
(133 reference statements)
1
6
0
Order By: Relevance
“…Consistent with this localization, Hrr25 was detected in immunoprecipitates with several different P-body proteins ( Figure 1C; Figure S1B). Previous largerscale studies had identified potential interactions between Hrr25 and particular P-body constituents (Ito et al 2001;Ho et al 2002;Cary et al 2015). Moreover, we found that the mammalian ortholog of Hrr25, CK1d, was also found in P-body foci ( Figure 1D).…”
Section: Resultssupporting
confidence: 60%
“…Consistent with this localization, Hrr25 was detected in immunoprecipitates with several different P-body proteins ( Figure 1C; Figure S1B). Previous largerscale studies had identified potential interactions between Hrr25 and particular P-body constituents (Ito et al 2001;Ho et al 2002;Cary et al 2015). Moreover, we found that the mammalian ortholog of Hrr25, CK1d, was also found in P-body foci ( Figure 1D).…”
Section: Resultssupporting
confidence: 60%
“…We conclude that multiple proteins of intermediary metabolism show substantially increased RNA association upon sorbic acid exposure. Notably, a set of metabolic enzymes were previously reported to accumulate in P‐bodies and stress granules during stress response (Cary et al , ; Jain et al , ). Seven of these enzymes showed increased RNA interactions in PAR‐TRAPP following sorbic acid treatment, while none showed reduced interactions.…”
Section: Resultsmentioning
confidence: 99%
“…We conclude that multiple proteins of intermediary metabolism show substantially increased RNA association upon sorbic acid exposure. Notably, a set of metabolic enzymes were previously reported to accumulate in P-bodies and stress granules during stress response (Cary et al, 2015;Jain et al, 2016). Seven of these enzymes showed increased RNA interactions in PAR-TRAPP following sorbic acid treatment, while none showed reduced interactions.…”
Section: Trapp Reveals Dynamic Changes In Rna-protein Interaction Folmentioning
confidence: 97%